Does the Failure of the Expectations Hypothesis Matter for Long‐Term Investors? - SANGVINATSOS, ANTONIOS; WACHTER, JESSICA A. (Journal of Finance, 2005)
ABSTRACT We solve the portfolio problem of a long‐run investor when the term structure is Gaussian and when the investor has access to nominal bonds and stock. We apply our method to a three‐factor model that captures the failure of the expectations hypothesis. We extend this model to account for time‐varying expected inflation, and estimate the model with both inflation and term structure data. The estimates imply that the bond portfolio of a long‐run investor looks very different from the portfolio of a mean‐variance optimizer. In particular, time‐varying term premia generate large hedging demands for long‐term bonds.